Assessment of hemodialysis stressors among patients undergoing maintenance hemodialysis - Dhanya Michael; Molly John; Usha Samuel; G. Lakshmi (MGM Journal of Medical Sciences, 2024)
Background: Hemodialysis patients often face considerable physical and psychosocial stressors, which can negatively impact their quality of life. This study aims to assess these stressors among hemodialysis patients in selected hospitals in Kerala, India. Materials and Methods: A cross-sectional, quantitative study was conducted with 222 hemodialysis patients. Participants were chosen through purposive sampling based on predefined inclusion criteria. Data were collected using self-reported methods, employing the validated Hemodialysis Stressor Scale to evaluate 32 physical and psychosocial stressors. Descriptive statistics were used to summarize demographic data and stressor scores, whereas correlation analysis was conducted to identify relationships between variables. Results: The most frequently reported physical stressors were arterial and venous punctures [mean (M) = 1.4, standard deviation (SD) = 1.1] and muscle cramps (M = 0.97, SD = 0.72). For psychosocial stressors, fluid restrictions (65.3%, M = 2.49, SD = 0.80) and dietary limitations (54.1%, M = 2.21, SD = 1.00) were the most prominent. Correlation analysis showed a moderate association between age and both physical and psychosocial stressors, with older patients experiencing higher levels of stress. Conclusion: The study highlights that fluid and dietary restrictions are hemodialysis patients’ most significant psychosocial stressors, whereas arterial and venous punctures are key physical challenges. These findings underscore the importance of developing interventions to reduce these stressors and improve patients’ quality of life.